2016
DOI: 10.1371/journal.pone.0163239
|View full text |Cite
|
Sign up to set email alerts
|

The Global Research Collaboration of Network Meta-Analysis: A Social Network Analysis

Abstract: Background and ObjectiveResearch collaborations in biomedical research have evolved over time. No studies have addressed research collaboration in network meta-analysis (NMA). In this study, we used social network analysis methods to characterize global collaboration patterns of published NMAs over the past decades.MethodsPubMed, EMBASE, Web of Science and the Cochrane Library were searched (at 9th July, 2015) to include systematic reviews incorporating NMA. Two reviewers independently selected studies and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
(51 reference statements)
1
33
1
1
Order By: Relevance
“…In the absence of clinical heterogeneity (determined by RXZ and JHT), the pooled prevalence with a 95% con dence interval (CI) of depression, anxiety, delirium, and PTSD will be calculated by using random-effects model to minimize the effect of between-study heterogeneity separately [22,23]. The statistical heterogeneity will be examined using I² statistic, with an I 2 of more than 75% indicating substantial heterogeneity [23,24], and the Cochran's Q and the Tau2 will also be reported with a P-value of < 0.05 considered statistically signi cant (heterogeneity). The publication bias will be examined using the Egger's test or the symmetry of the funnel plot.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of clinical heterogeneity (determined by RXZ and JHT), the pooled prevalence with a 95% con dence interval (CI) of depression, anxiety, delirium, and PTSD will be calculated by using random-effects model to minimize the effect of between-study heterogeneity separately [22,23]. The statistical heterogeneity will be examined using I² statistic, with an I 2 of more than 75% indicating substantial heterogeneity [23,24], and the Cochran's Q and the Tau2 will also be reported with a P-value of < 0.05 considered statistically signi cant (heterogeneity). The publication bias will be examined using the Egger's test or the symmetry of the funnel plot.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, meta-analyses on antidepressant drugs are far less likely to report negative statements, if review authors have conflicts of interest 35. Pharmaceutical companies are regularly involved in performing network meta-analyses,5 and in one survey, 19 contracting companies reported that they had performed a total of 476 network meta-analyses, only to publish 102 of them (21%) 36. Research on the impact of industry sponsorship and publication bias on treatment rankings in network meta-analyses is urgently needed.…”
Section: Treatment Rankingsmentioning
confidence: 99%
“…Recent upsurge in the production and scientific collaborations of network meta-analyses also indicate increased interest among authors to take advantage of its possibilities 5. However, to deem it the highest level of medical evidence,6 may be premature.…”
Section: The Way Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…La conformación de redes, puede ser analizada con base en sus propiedades estructurales; se mencionan, la densidad que valora la cantidad promedio de lazos, así como la existencia y funcionamiento de los grupos de interés y sus compromisos formales, esto determina los grados de conectividad; igualmente, se considera la cercanía, capacidad de un actor para alcanzar e influenciar a todos los nodos de la red; mientras que la centralidad, atiende a los nodos más importantes, como espacio de confluencia de múltiples flujos, permite identificar los actores que ejercen un mayor poder/mayor motricidad sobre la totalidad del sistema. Desde los aportes deBorgatti (2005), Bakkalbasi yKrichel (2006),Bozdogan (2013),Robinson et al, (2013),Li et al, (2016), la motricidad del sistema está asociada a la posición ventajosa, según grado de centralidad, que tiene un actor sobre los demás; implica una mayor influencia o conexión con el resto de actores; permite identificar los nodos más determinantes en función de su impacto que forman parte de la red.Por su parte, Villanueva-Felez, Fernández-Zubieta y Palomares-Montero (2014), retoman las ideas expuestas porUzzi (1997), para destacar que en el análisis de redes, además de atender el componente estructural, se debe observar la dinámica funcional -relacional, en una dimensión personal (actores) y otra organizacional. Los principios de integración, convergencia, complementariedad e integración entre ambas dimensiones preconfiguran formas de comportamiento; de allí que, el perfil individual de los actores incide de forma significativa en las cualidades de la producción científicatécnica; por su parte, la dinámica de la red como totalidad institucional afecta su carácter cuantitativo.Fundamentado en las vías de conectividad para impulsar el acercamiento entre actores, el análisis de redes supone la conceptualización de una interfaz, como espacio de interacción donde se representan los flujos que en múltiples direcciones y sentidos, permiten el acercamiento y vías de conectividad entre los nodos centrales y periféricos.…”
unclassified